Comparative phylogeography of five swallowtail butterfly species (Lepidoptera: Papilionidae) in South Africa : ecological and taxonomic implications. - Neef, Götz-Georg (Rhodes University, Faculty of Science, Botany Department, 2014)
With current biota under constant threat of extinction, it is important to ascertain where and how biological diversity is generated and partitioned. Phylogeographic studies can assist in the identification of places and processes that indicate the origin and maintenance of biodiversity. Forest fragmentation has a big effect on local extinction and loss of genetic diversity of forest-restricted taxa, along with divergence and speciation of forest biota. This study aims to understand the effects of these processes on a number of forest-dwelling butterflies using a comparative phylogeographic approach. Mitochondrial DNA of five different Papilio species with different degrees of forest specificity was analysed using phylogenetic methods. In addition, the subspecific taxonomy of P. ophidicephalus was investigated using morphometrics of discal spots on the wings and nuclear DNA analysis along with mitochondrial DNA analysis. The results show that the forest-restricted species (P. ophidicephalus and P. echerioides) have more genetic structure and less genetic diversity than the more generalist species (P. dardanus, P. demodocus and P. nireus). This could be due to inbreeding depression and bottlenecks caused by forest fragmentation. As forest patches become smaller, the population size is affected and that causes a loss in genetic diversity, and increasing habitat fragmentation disrupts gene flow. The intraspecific taxonomy of P. ophidicephalus is far from revealed. However, this study shows there is evidence for the different subspecies when comparing morphological results and genetic results. From the evidence provided here it is suggested that P. ophidicephalus should be divided into two separate species rather than five subspecies.
Keywords: Swallowtail butterflies; Papilionidae -- South Africa; Phylogeography -- South Africa; Swallowtail butterflies -- Effect of habitat modification on; Biodiversity -- South Africa